Emotional exhaustion in cancer clinicians: A mixed methods exploration - Daruvala, Rhea; Ghosh, Maupali; Fratazzi, Francesca; Norzan, Siti Adibah; Laha, Anirban; Ahmed, Rosina; Panda, Samiran; Datta, Soumitra Shankar (Indian Journal of Medical and Paediatric Oncology, 2019)
Objectives: The aim of the current study was to explore the associations of emotional exhaustion in oncology clinicians and perceptions of doctors about their work–life balance in a developing country. Methods: The current study used quantitative semi-structured interviews and qualitative in-depth interviews to explore emotional exhaustion and burnout in doctors in a tertiary care cancer center. Sociodemographic details, Maslach Burnout Inventory, and Patient Health Questionnaire were used for the quantitative analysis. Results: Increased work pressure (adjusted odds ratio [AOR]: 5.39, 95% confidence interval [CI]: 2.01–14.47, P < 0.01), reduced job-related satisfaction (AOR: 3.56, 95% CI: 1.37–9.25, P < 0.01), being a woman (AOR: 3.4, 95% CI: 1.2–9.5, P < 0.01), and having higher anxiety and depression scores (AOR: 2.89, 95% CI: 1.11–7.46, P = 0.03) were independently associated with higher levels of emotional exhaustion. In the qualitative interviews, many doctors felt working in oncology a satisfying as well as stressful experience. Dealing with palliative and end-of-life situations and counseling patients and their family members about various treatment options contributed to the stress. Male and female clinicians viewed work–life balance differently. Female doctors charted a larger area of influence for which they felt responsible in work and life. Conclusion: Increased work pressure, reduced job satisfaction, and increased affective symptoms contribute to emotional exhaustion in oncology clinicians, and the risk increases especially in female doctors. Having gender-sensitive and employee-friendly policies will likely help in having a nurturing work environment.
Keywords: Burnout; cancer; depression; emotional exhaustion; oncology; work-life balance